Anti-EGFR Therapy in Metastatic Small Bowel Adenocarcinoma: Myth or Reality?. (August 2020) - Dell'Aquila, Emanuela; Zeppola, Tea; Stellato, Marco; Pantano, Francesco; Scartozzi, Mario; Madaudo, Cristina; Pietrantonio, Filippo; Cremolini, Chiara; Aprile, Giuseppe; Vincenzi, Bruno; Moretto, Roberto; Puzzoni, Marco; et al.
Background: Due to the relative rarity of small bowel adenocarcinoma (SBA), prospective trials, helping to guide therapeutic decisions, are lacking and the optimal therapy for advanced SBA is unknown. The role of targeted agents, such as anti–epidermal growth factor receptor (EGFR) and anti–vascular endothelial growth factor (VEGF), is unknown. Patients and Methods: This is a retrospective multicenter observational study that included patients with metastatic SBA treated with anti-EGFR antibodies (cetuximab or panitumumab) ± chemotherapy in the first (I) or second (II) line. Results: Thirteen patients with metastatic SBA, recruited from 5 Italian referral institutions, were included in the present retrospective analysis. All patients received anti-EGFR inhibitors as a single agent or in association with chemotherapy. More common G2 treatment–related side effects were skin reaction (8 patients, 53.8%), hypomagnesemia (6 patients, 46.2%), and diarrhea (8 patients, 61.5%). Grade 3 diarrhea was observed in only 1 patient. Conjunctivitis was not reported in any patients. Grade 4 toxicity was not reported. In the overall population, median progression-free survival was 5.526 months (95% confidence interval [CI]: 3.684-12.467). Median overall survival was 15.86 months (95% CI: 14.43-24.30). Complete response was observed in 15% of patients, partial response in 39% of patients, stable disease in 23% of patients, and progression disease in 15% of patients. Conclusions: In this retrospective analysis, anti-EGFR inhibitors showed to be a suitable addendum to chemotherapy in the I and II line, with an excellent tolerance and safety profile both in I and II line.